EFL STUDENTS’ PERCEPTION TOWARDS EXTENSIVE READING PRACTICES IN HIGHER EDUCATION LEVEL (RETAIN, 2020)
Abstract Extensive reading practices which considered as reading for pleasure and search for general information is an important program to be implemented by EFL (English as a Foreign Language) students in Indonesia, especially for students in higher education in which English is as their major. Extensive reading practices have been proven by the previous study that it could improve EFL (English as a Foreign Laguage) students’ English skills; therefore, this study aimed to investigate the students’ perceptions in relation to their extensive reading subject, kinds of materials that they preferred, and its benefit to their English skills. This study was conducted in Universitas Negeri Surabaya whereby the researcher selected ten senior English department students who have already received the extensive reading subject in their previous semesters. This study used a qualitative method with a semi-structure interview as an instrument. The result of this study showed that the students have good perceptions towards extensive reading practices in which they considered if extensive reading is a reading activity for pleasure and information search where they can read material without any restraint. Novel (fiction genres), news, and journal were the materials that the students chose when they implemented extensive reading practices. Besides, extensive reading practices also contributed to the enhancement of their knowledge and English skills such as writing, speaking, listening, reading, vocabulary mastery, and grammar. In addition, some suggestions were given to the students to continually implement extensive reading as one of their habits in their daily activity.